Mending the imaginary wall between Indonesia and Malaysia; The case of maritime delimitation in the waters off Tanjung Berakit - Arsana, I Made Andi (Wacana, Journal of the Humanities of Indonesia, 2011)
Due to its geographical location, Indonesia shares border areas with at least ten neighbouring countries with which maritime boundaries must be settled. As of March 2011, Indonesia is yet to finalize its maritime boundaries with various States including Malaysia with which four maritime boundaries need to be settled: the Malacca Strait, the South China Sea, the Sulawesi Sea, and the Singapore Strait (off Tanjung Berakit). It is evident that pending maritime boundaries can spark problems between Indonesia and Malaysia. The dispute over the Ambalat Block in 2005 and 2009 and an incident in the waters off Tanjung Berakit on 13 August 2010 are two significant examples. This paper discusses the incident in the waters off Tanjung Berakit, but will be preceded by a description of the principles of coastal States' maritime entitlement pursuant to international law of the sea. Following the discussion, this paper provides suggestions for settling maritime boundaries in the area from technical/geospatial and legal perspectives.